DISCOURSE ANALYSIS: ADJACENCY PAIRS ANALYSIS OF CONVERSATION BETWEEN NAJWA SHIHAB, SULE AND ANDRE ON "THE BEST OF INI TALKSHOW" EVENT - Asyuni Pranika, Ni Luh Dian (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2023)
Conversation is one of our activities in communicating. As social beings, it isimportant for us to be able to interact with each other in order to strengthen arelationship. To understand more deeply the conversation, it can be done with ananalytical model. One of the analyzes that we can use is the analysis of adjacency pairs which according to Yule is included in the study. Adjacency pair is a two-part exchange where the first utterance is functionally dependent on the response of the secondutterance. Using adjacency pairs can help us to more easily analyze the conversationsor communications that we do. This study aims to determine the feedback between the conversations that have been carried out. In a conversation there is a need for reciprocitybetween the questioner and the answerer so that the conversation can be said to go well.Data collection is done by observing and watching methods. In short, the results of thisstudy are useful as input for people who are having conversations. In this research,Conversation Analysis Theory is used to analyze a talk show between Najwa Shihab,Andre and Sule on "The Best Of Ini Talkshow"